Analysis of clinical and laboratory parameters affecting testosterone dynamics in men with ankylosing spondylitis and psoriatic arthritis: Results of a pilot observational study - T. S. Panevin; T. V. Korotaeva; T. V. Dubinina; E. G. Zotkin; A. M. Lila; Yu. I. Korsakova; L. D. Vorobyeva; E. M. Agafonova; S. I. Glukhova; E. L. Nasonov (Rheumatology Science and Practice, 2026)
Men with spondyloarthritis (SpA) are characterized by a high incidence of hypogonadism (low testosterone levels). Hypogonadism is associated with higher indicators of systemic inflammation and metabolic disorders. The aim – to compare the dynamics of spondyloarthritis activity with changes in total testosterone (TT) levels in men with ankylosing spondylitis (AS) and psoriatic arthritis (PsA). Materials and methods . Thirty-six men with AS and 47 men with PsA were included. All patients had their TT levels measured at baseline and during follow-up (on average, after 14.5 [12.8; 17.3] months for AS and 14.0 [9.5; 19.0] months for PsA). Subgroups were identified based on the presence/absence of decreased BASDAI (Bath Ankylosing Spondylitis Disease Activity Index) and DAPSA (Disease Activity in Psoriatic Arthritis) indices, as well as C-reactive protein (CRP) levels. A comparative assessment of quantitative and qualitative indicators reflecting the clinical features of AS and PsA was conducted at baseline and over time, as well as a correlation analysis between the studied quantitative indicators over time. Results. An inverse correlation was found between changes in testosterone levels and CRP (ρ=–0.4; p=0.015) in patients with AS. In PsA, no significant correlations were found between changes in TT levels and changes in indicators reflecting activity. In patients with AS, with decreased BASDAI activity, no significant changes in TT levels were observed. At the same time, a decrease in CRP from 9.6 [2.7; 33.9] to 1.9 [0.65; 8.5] mg/L (p